An Evaluation of the Impact of Global Health Training Programs in Obstetrics and Gynecology Residency Programs [3M]. (May 2018) - Trivedi, Shivika; Haddad, Lisa; Narvaez, Jennifer; Walker, Elizabeth; Jamieson, Denise J.; Lathrop, Eva
Abstract : INTRODUCTION: Although the number of Global Health Training (GHT) programs in obstetrics and gynecology (OB/GYN) residencies has increased, few studies exist describing their programmatic work. We aimed to evaluate the contributions of GHT programs by assessing impact, reciprocity and whether global health goals were addressed. METHODS: This cross-sectional observational study identified all U.S. OB/GYN residencies with GHT programs and evaluated the publications resulting from them. Eligible articles included those published in 2009-2014 about work done in a GHT location by GHT faculty. All eligible articles were used to calculate an H-index for each institution as a proxy for impact. The inclusion of host authors on articles served as a proxy for reciprocity. Article content was assessed to evaluate whether programs addressed Millennium Development Goals (MDG). RESULTS: Among 245 OB/GYN residencies, 193 (80%) had GHT programs. Of these, 26 (14%) had faculty who had published articles meeting inclusion criteria and the H-indices per institution ranged from zero to 17. Of 698 articles reviewed, 95% of articles included one or more host country authors and 78% addressed at least one MDG, including 39% that addressed improving maternal health (MDG 5). CONCLUSION: Most OB/GYN residencies are offering GHT. The majority of programmatic work addresses MDG and thus is aligned with global health priorities. The impact and reciprocity of GHT programs varies across institutions. Residencies could benefit from internal analysis of their GHT programs to evaluate if knowledge gained is being disseminated, and to ensure equitable partnerships and the creation of sustainable, impactful initiatives.